ANALISIS PENGARUH CELEBRITY ENDORSE RIZKY FEBIAN TERHADAP MINAT PEMBELIAN PRODUK TEH KOTAK RASA BUAH (STUDI KASUS PADA MASYARAKAT KABUPATEN BANTUL) - Intan, Danti Shela; Hardjanti, Sri (Jurnal Fokus Manajemen Bisnis, 2020)
Celebrity endorser has become one popular approach for marketing communication. This study aims to determine the effect of using celebrity endorser on customer’s buying intentions. This study focus on variables on celebrity endorser which are trust, honesty, and attractiveness and their effect on customer’s buying intentions. Object of this study are customers of fruit flavored tea product. Data collection technique is questionnaire that are distributed to customers at productive age in Bantul Regency Yogyakarta. By using SPSS to analyze the data, this study found that Celebrity Endorser’s variables which are trust, honesty, and attractiveness have a positife effect on customer’s buying interest.